Labor Market Shocks, Social Protection and Women's Work - Nikita Sangwan; Swati Sharma (Queen's University Belfast, Queen's Business School, 2024)
The COVID-19 pandemic highlighted the vulnerabilities women encounter in labor markets worldwide. We investigate the potential of social protection measures in mitigating declines in women's labor market participation. Specifically, we look at the Indian context, where lockdowns spurred a reverse migration of male workers from urban to rural areas, exerting pressure on rural labor markets. Despite a 6% rise in reliance on India's largest demand driven employment guarantee scheme, our analysis reveals a 0.4% decrease in women's participation during the pandemic, equivalent to a loss of 11,500 person-days of work. However, a gender quota provision helped sustain women's employment status. In districts where the reservation quotas had not been exhausted pre pandemic, women's share in public works increased by 2.7%. Our findings underscore the need for mandated provisions and targeted programs for women to counteract labor market withdrawals and bolster overall labor market participation in times of crisis.
Keywords: J08; J16; O15; 330; Covid-19; Rural labor market; Gender; Reverse migration; MGNREGA; GKRA